Misdiagnosis of asthma and COPD and underuse of spirometry in primary care unselected patients - Heffler, Enrico; Crimi, Claudia; Mancuso, Salvatore; Campisi, Raffaele; Puggioni, Francesca; Brussino, Luisa; Crimi, Nunzio (Respiratory medicine, 2018)
The diagnosis of both asthma and chronic obstructive pulmonary disease (COPD) consists of a combination of classical symptoms and signs, and the evidence of consistent lung function abnormalities. Spiromety has been reported to be underused, possibly for practical difficulties in accessing to a lung function lab. This may lead to misdiagnosis of both asthma and COPD. We aimed to evaluate the frequency of spirometry use and the concordance between doctor-diagnosed asthma and COPD and spirometric patterns, in an unselected cohort of patients sent by general practitioners to perform a spirometry. The first 300 patients consecutively enrolled patients performed spirometry and bronchodilator test with salbutamol 400 mcg. Demographic, clinical and lung function data have been collected. 128 patients (42.7%) declared a doctor-diagnosed asthma and 75 (25%) a doctor-diagnosis of COPD; the remaining subjects never had received any respiratory diagnosis. Only 112 patients with doctor-diagnosed asthma (55.2%) and 114 (56.2%) with doctor-diagnosed COPD have ever performed a spirometry in their entire life (average time since the last spirometry was about 47.0 months). Eighty-nine (69.5%) and 10 (13.3%) patients with respectively doctor-diagnosed asthma and COPD had concordant spirometric patterns with their known diseases. we described a worrying lack of use of spirometry and a high proportion of misdiagnosis, in patients with suspect chronic airway inflammatory diseases and cared by primary care physicians. Novel strategies to overcome this situation include should be implemented to give a better care to our patients. •The diagnosis of asthma and COPD is a combination of symptoms, signs, and the evidence of consistent lung function abnormalities.•Lung function testing is still worryingly underused even in lower airway inflammatory disorders affected patients.•This study confirms that primary care patients often received diagnosis of asthma or COPD without having ever perfomed a spirometry.•The lack of spirometric evaluation in the diagnostic algorithm of asthma and COPD leads to great proportion of misdiagnosis.